2013
DOI: 10.1002/ijc.28604
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antitumor effect of an intracellular single‐chain antibody fragment against the E7 oncoprotein of human papillomavirus 16

Abstract: Human papillomavirus (HPV)-associated tumors still represent an urgent problem of public health in spite of the efficacy of the prophylactic HPV vaccines. Specific antibodies in single-chain format expressed as intracellular antibodies (intrabodies) are valid tools to counteract the activity of target proteins. We previously showed that the M2SD intrabody, specific for the E7 oncoprotein of HPV16 and expressed in the endoplasmic reticulum of the HPV16-positive SiHa cells, was able to inhibit cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
(68 reference statements)
1
31
0
Order By: Relevance
“…Notably, no difference in the rate of tumor growth occurred in TgN(Tie2-hPTX3) animals grafted with FGF-independent TC-1 or C3 cancer cells ( Figure S2A) (Accardi et al, 2014). Similarly, hPTX3 overexpression did not affect the growth of FGFR1-TRAMP-C2 lesions transduced with a constitutively activated form of the intracellular FGFR1 TK domain (Hart et al, 2000) and characterized by a faster rate of growth when compared to parental TRAMP-C2 tumors ( Figure S2B).…”
Section: Generation Of Transgenic Hptx3-expressing Tgn(tie2-hptx3) Micementioning
confidence: 93%
“…Notably, no difference in the rate of tumor growth occurred in TgN(Tie2-hPTX3) animals grafted with FGF-independent TC-1 or C3 cancer cells ( Figure S2A) (Accardi et al, 2014). Similarly, hPTX3 overexpression did not affect the growth of FGFR1-TRAMP-C2 lesions transduced with a constitutively activated form of the intracellular FGFR1 TK domain (Hart et al, 2000) and characterized by a faster rate of growth when compared to parental TRAMP-C2 tumors ( Figure S2B).…”
Section: Generation Of Transgenic Hptx3-expressing Tgn(tie2-hptx3) Micementioning
confidence: 93%
“…This result is particularly interesting because C3 model is more resistant than widely used TC-1 to specific immunotherapy. 31 Indeed, anti E7 vaccine was less effective in this model in respect to TC-1 model. This anticancer activity of E5 vaccines is linked to specific immune response and in particular to a higher E5-induced activity in CD4C circulating lymphocytes.…”
Section: Discussionmentioning
confidence: 80%
“…154 Initial testing showed that the exosomes derived from cells transfected with plasmids expressing an Nefmut-anti-16E7 scFv fusion protein, contained the antibody in an active E7-binding conformation which performed the same as scFv delivered as DNA or protein. 154,155 These antibody-containing exosmes could be used to treat lesions situated not only on the cervix, but also on the anogenital region or in the oropharynx. Although these findings are promising, more widespread clinical application will require improved standardized techniques to purify the exosomes and monitor the exosomal contents.…”
Section: Use Of Micrornas and Exosomes For Treatment Of Hpv-positive mentioning
confidence: 99%